Pengendalian Internal, Budaya Organisasi, dan Audit Internal terhadap Fraud di Pemerintah - Natasya Agustine; Endah Susilowati (Journal of Management and Bussines (JOMB), 2022)
This study aims to test and prove the impact of internal control, organizational culture, and internal audit on fraud in the Sidoarjo district government. The research method used is quantitative method, the data used is primary data. Data collection method in the form of a questionnaire. The population in this study were 26 agencies and offices in Sidoarjo district. The sample in this study used a simple random sampling technique using the slovin formula so that a sample of 96 was obtained. The processing method used was multiple linear regression. The results showed that the internal control variables showed sig. of 0.009 which means <0.05; b) organizational culture variable shows sig. of 0.001 which means <0.05; c) the internal audit variable shows sig. of 0.000 which means <0.05. In conclusion, internal control, organizational culture, and internal audit contribute to reducing fraud. The biggest impact is internal audit, the better the internal audit is carried out, the lower the fraud will be. Keywords: Internal Audit, Organizational Culture, Fraud, Internal Control